Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) dalam Kerangka Kepastian Hukum Berdasarkan Undang-Undang Perlindungan dan Pengelolaan Lingkungan Hidup - Didin Maulidina; Suwari Akhmaddhian (Universitas Kuningan, 2025)
The management of Hazardous and Toxic Materials (B3) waste is highly urgent in maintaining environmental sustainability and public health, and is part of the constitutional rights of Indonesian citizens. This study aims to analyze the implementation of the principle of legal certainty in B3 waste management, with a case study of the agreement between PT Honda Precision Parts Manufacturing and PT Cipta Jaya Hakiki. The method used is a juridical-normative method with a literature study approach to relevant laws and regulations. The results of the study indicate that B3 waste management in Indonesia has been regulated through Law No. 32 of 2009 and Government Regulation No. 22 of 2021, which require official permits for every business entity involved. However, in practice, legal violations were found because PT Cipta Jaya Hakiki did not have an official permit but continued to carry out B3 waste management activities based on a power of attorney from PT Lut Putra Solder. This creates a legal flaw in the agreement involving elements of naturalia and accidentalia, and violates the principles of legality and legal certainty. This study recommends that the government strengthen supervision, enforce legal sanctions strictly, and provide education and verification to business actors to ensure compliance with regulations. Thus, hazardous waste management can be carried out legally, responsibly, and sustainably.